Palladium-Catalyzed C–H Arylation of 1,2,3-Triazoles - Chengwei Zhang (Molecules, 2016)
Palladium(II) acetate, in combination with triphenylphosphine, catalyzes direct arylation of 1,4-disubstituted 1,2,3-triazoles effectively. This C–H arylation reaction provides facile access to fully substituted triazoles with well-defined regiochemistry.